Succussed Serial Dilutions in Water Carry Solute Information via Solute-Specific Water Structures—A Theory Based on Quantum Electrodynamics - Maity, Tanmoy; Mahata, C.R. (Homeopathy, 2021)
Active ingredients are unlikely to be present in homeopathic dilutions that surpass the Avogadro limit. Yet responses of biological systems to these substances—chemically equivalent to water and indistinguishable from one another—are specific to the materials that are diluted away. This article addresses this challenging problem of homeopathy by identifying its underlying cause through a quantum electrodynamics-based “structural model” stated as: Succussed serial dilutions in water carry information about the solute via solute-specific water structures. The model is verifiable by our three-stranded set of experiments—nuclear magnetic resonance spectroscopy, anomalous dielectric dispersion, and atomic force microscopy. The results, some of which are presented here, directly or indirectly indicate that even extremely diluted solutions, devoid of any gross presence of the solutes, contain solute-reminiscent water structures. Apart from contributing to understanding high-dilution phenomena, these findings are expected to create an impact in the areas of medicine, pharmacopeia, and biology. Succussed aqueous dilutions acquire altered water structures with change of starting material: thus, their altered properties may be ascribed to these water structures, akin to allotropes of carbon. This theory justifies water structures as potential information carrier through succussed serial dilutions.
Keywords: succussed serial dilution; Avogadro limit; altered physico-chemical properties; water structures; structural model